Mozambique Public Expenditure Review : Addressing the Challenges of Today, Seizing the Opportunities of Tomorrow - World Bank (Washington, DC, 2015)
Mozambique's economy has experienced strong and sustained growth since the end of the country s civil war in 1992. Over time, the sources of revenues are changing, bringing both opportunities and challenges for fiscal management. The government has loosened fiscal policy in the past few years, and the current fiscal stance does not appear sustainable. Public spending is projected at almost 42 percent of gross domestic product (GDP) in 2014, and the deficit after grants is expected to widen to over 9 percent of GDP. These fiscal consolidation efforts will require reprioritizing expenditures and increasing the efficiency of spending, to ensure sufficient resources are allocated to priority sectors. Looking ahead, substantial resource revenues expected toward the end of the decade present an unprecedented opportunity but this will need to be well managed. The 2001 and 2003 public expenditure reviews indicated that a number of financial management reforms are required, which the government successfully implemented. However, it is important to build on this progress to ensure that the government is sufficiently prepared to address the challenges ahead. Given external economic shocks and the possibility of weaker commodity prices, resource revenues can be delayed or reduced. Therefore, it will be important to adopt a prudent fiscal stance in the medium term to adequately prepare for the changes ahead.